Predictive Factors for a Long Hospital Stay in Patients Undergoing Laparoscopic Cholecystectomy - Wasana Ko-Iam (2018)
ï¿½ 2017 Wasana Ko-iam et al. Background. Although the advantages of laparoscopic cholecystectomy (LC) over open cholecystectomy are immediately obvious and appreciated, several patients need a postoperative hospital stay of more than 24 hours. Thus, the predictive factors for this longer stay need to be investigated. The aim of this study was to identify the causes of a long hospital stay after LC. Methods. This is a retrospectiv e cohort study with 500 successful elective LC patients being included in the analysis. Short hospital stay was defined as being discharged within 24 hours after the operation, whereas long hospital stay was defined as the need for a stay of more than 24 hours after the operation. Results. Using multivariable analysis, ten independent predictive factors were identified for a long hospital stay. These included patients with cirrhosis, patients with a history of previous acute cholecystitis, cholangitis, or pancreatitis, patients on anticoagulation with warfarin, patients with standard-pressure pneumoperitoneum, patients who had been given metoclopramide as an intraoperative antiemetic drug, patients who had been using abdominal drain, patients who had numeric rating scale for pain > 3, patients with an oral analgesia requirement > 2 doses, complications, and private ward admission. Conclusions. LC difficulties were important predictive factors for a long hospital stay, as well as medication and operative factors.